Exploring the healthcare needs of patients with mild chronic obstructive pulmonary disease - Jácome, Cristina (2020)
Pulmonary rehabilitation is a core component of the management of patients with chronic obstructive pulmonary disease (COPD), however, patients are not referred until they have advanced COPD. Nevertheless, it is unknown if patients with mild COPD are also symptomatic and experience restrictions in their daily life.